Pemanfaatan Media Audio Visual sebagai Sarana Pembelajaran Interaktif di Sekolah Dasar : Strategi, Manfaat, dan Implementasinya - Hamida Azzahra; Chandra Chandra; Inggria Kharisma (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2025)
In the learning process in Elementary Schools (SD), the use of audio media is one of the innovative approaches that can increase the efficiency and interactivity of learning. The purpose of this article is to thoroughly study the use of audio media as an interactive learning tool in SD. This review includes ways to implement it, the benefits obtained, and the problems and solutions that arise when implementing it. The discussion method is carried out by conducting literature research and analyzing learning practices applied in several elementary schools. Audio media, such as podcasts, educational songs, audiobooks, and sound recordings, can increase student engagement, strengthen their understanding of the material, and support auditory learning styles. In addition, this media can be used in various fields of education, especially English, Indonesian, and Religious Education. However, there are still several problems that hinder the use of audio media. These include limited facilities, lack of teacher instruction, and student readiness to listen actively. As a result, the right approach is needed. These strategies include creating interesting audio content, incorporating it into learning activities, and improving teachers' ability to utilize educational technology. Audio media can help elementary school students get a fun and meaningful learning experience if used in a targeted and creative way.